Implicit Maternal Intuition Confidence Is Associated With Maternal Well-Being Across Cultures - Gardner, Wendi L.; Rotella, Katie N.; Nikolovski, Janeta (Frontiers in Psychology, 2020)
The transition to motherhood involves the experience of each individual mother and child, as well as the burden of cultural expectations. Social desirability demands may impede self reports of difficulties during the transition to motherhood when using traditional explicit measures. One core component of maternal role attainment is a mother’s confidence in her own intuitive knowledge of her child. This brief report presents two studies that examine a “low technology” implicit measure of maternal intuition confidence that is based within a more general decision confidence paradigm. Study 1 examined the association of both implicit and explicit maternal intuition confidence with depressive symptoms, life satisfaction, and maternal identity satisfaction in a U.S. sample of mothers. The implicit measure contributed to variance in each of the outcome measures, above and beyond an explicit measure. Study 2 explored the association of implicit maternal intuition confidence with life satisfaction and maternal identity satisfaction in Brazil, China, India, the U.S. and the U.K. Across all samples, implicit maternal intuition confidence was significantly associated with satisfaction with life. However, it was significantly associated with maternal identity satisfaction only in the two individualistic countries (the U.S. and the U.K.), but not in the three collectivist countries.